1992
DOI: 10.1007/bf01989980
|View full text |Cite
|
Sign up to set email alerts
|

Effect of subinhibitory concentrations of cefamandole and cefuroxime on adherence ofStaphylococcus aureus andStaphylococcus epidermidis to polystyrene culture plates

Abstract: The ability of cefamandole and cefuroxime to inhibit adherence of staphylococci to polystyrene culture plates was tested in an in vitro assay using eight strains each of Staphylococcus aureus and Staphylococcus epidermidis. The results indicated that subinhibitory concentrations of cefamandole and cefuroxime altered the adherence ability of both staphylococcal species, inhibition of adherence being more marked in the presence of cefamandole. It may be important to consider antiadherence properties in associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Enhanced biofilm formation in the presence of sub-MICs of antibiotics is a common phenomenon among bacteria and is thought to result from a global response to cell stress (7). Other studies found an inhibitory effect or no effect on S. aureus biofilm formation by sub-MICs of other cell wall-active antibiotics (cefamandole, cefuroxime, nafcillin, teicoplanin, and vancomycin) and protein synthesis inhibitors (tetracycline and roxithromycin) (5, 6, 8, 9). Most of these studies, however, utilized a single strain of S. aureus and tested antibiotics at a single or limited number of antibiotic concentrations, usually ≤1/2× MIC.…”
Section: Introductionmentioning
confidence: 97%
“…Enhanced biofilm formation in the presence of sub-MICs of antibiotics is a common phenomenon among bacteria and is thought to result from a global response to cell stress (7). Other studies found an inhibitory effect or no effect on S. aureus biofilm formation by sub-MICs of other cell wall-active antibiotics (cefamandole, cefuroxime, nafcillin, teicoplanin, and vancomycin) and protein synthesis inhibitors (tetracycline and roxithromycin) (5, 6, 8, 9). Most of these studies, however, utilized a single strain of S. aureus and tested antibiotics at a single or limited number of antibiotic concentrations, usually ≤1/2× MIC.…”
Section: Introductionmentioning
confidence: 97%
“…Several strategies have been proposed to inhibit biofilm formation on medical devices, including the administration of sub-MICs of antibiotics [5,12,17], use of furanone compounds [4], anti-inflammatory drugs [3], bacterial extracts [14], development of new anti-adhesive medical surfaces [8,22] and coating medical devices with several different compounds, including antibiotics [16,21,28].…”
Section: Introductionmentioning
confidence: 99%
“…The practical importance of these observations may be limited, since the adhesion substrates used are unlikely to be colonized by staphylococci in vivo. When po lystyrene surfaces were used as a substratum, adhesion of staphylococci was reduced by ce phalosporins, vancomycin and teicoplanin [24],…”
Section: Introductionmentioning
confidence: 99%